Life Expectancy and its Socioeconomic Determinants in Iran - Somayeh Delavari (Electronic Physician, 2016)
Introduction: Life expectancy at birth (LEB) is closely associated with the degree of economic and social development in developed and developing countries. This study aimed to examine the socioeconomic factors affecting LEB in Iran from 1985 to 2013. Methods: Time series analysis was used to examine the effects of key explanatory factors (GDP per capita, number of doctors per 10,000 population, degree of urbanization, food availability, CO2 emission, total fertility rate, inflation rate, and literacy rate) on LEB in Iran from 1985 to 2013. Study data were retrieved from the Central Bank of Iran (CBI), Iranian Statistical Center (ISC), and World Bank. Augmented Dickey Fuller (ADF) and Banergy, Dolado, and Master (BDM) tests, Engle Granger approach, and an ordinary least-square (OLS) model were used to achieve the aim of the study. Data analysis was performed by Stata V.12 software. Results: Our findings indicated that GDP per capita (p=0.003), number of doctors per 10,000 population (p=0.036), literacy rate (p=0.0001), and food availability (p=0.0001) have a positive and significant statistically effect on LEB. The relationship between total fertility rate and LEB was negative and significant (p=0.023). In addition, the effect of degree urbanization (p=0.811), CO2 emission (p=0.185), and inflation rate (p=0.579) on LEB were not significant. Conclusion: GDP per capita, number of doctors per 10,000 population, food availability, literacy rate, and total fertility were identified as the main factors affecting life expectancy in Iran. The study, however, suggests that life expectancy in Iran could be improved if attention is given to factors that reside outside of the health sector.